Azerbaycan anayasal yargı sisteminde ‘‘ şikayet’’ denetim usulü: anayasa şikayeti - Aliyev, Cabir (My University, 2010)
İkinci Dünya Savaşı’nın ardından insan hakları harekâtının uluslararası düzlemde gelişmesine koşut olarak ulusal düzeyde insan haklarını korumaya yönelik enstrüman olarak düşünülen anayasa şikayeti kurumu, çıkış noktası itibarı ile hukuk düzenini korumakla sınırlı görev icra eden anayasa yargısının fonksiyonunda evrime sebep olmuştur. Artık anayasa yargısının temel işlevlerinden birisi anayasanın üstünlüğünü sağlamaksa, bir diğeri de insan haklarını korumak olarak ifade edilebilir. İlke bazındaki bu gelişmenin pratik tezahürü olarak ortaya çıkan anayasa şikayeti kurumu, hukuk devleti ereğine ulaşmada da önemli katkılar sağlar. Bu çalışmada Azerbaycan ve Azerbaycan’la aynı gelenekten gelmesi hasebiyle Avrupa Birliğine üye postkomunist ülkelerden Çek Cumhuriyeti, Polonya, Letonya, Macaristan, Slovakya ve Slovenya’nın anayasa şikayetine ilişkin düzenlemeleri incelenmiş ve kurumun özgürlükçü hukuk devleti açısından katkısı tespit edilmeye çalışılmıştır.

After the World War II, in parallel to the spreading of the human rights movement in international level, the establishment of the institution for the constitutional complaints, aimed to be an instrument towards the protection of human rights in national level, has caused an evolution in function of the constitutional review, the emerging point of which has been the execution of the duty limited to the preservation of the juridical order. Now, while one of the basic functions of the constitutional review is to maintain the superiority of the constitution, the other one can be expressed as the protection of the human rights. The institution for the constitutional complaints, emerging as a practical appearance of this development on basis of principle, is significantly contributing to the aim of reaching the Rule of Law. In this thesis, the regulations regarding the constitutional complaints in Azerbaijan and post-communist countries like Czech Republic, Poland, Lithuania, Hungary, Slovakia and Slovenia, which share the same tradition with Azerbaijan, have been examined and the contribution of the institution to the libertarian Rule of Law has been attempted to be identified.
Keywords: Anayasa_Azerbaycan; Hukuk; Kamu Hukuku